Letters to Philippians, Colossians and Thessalonians - Barclay, William; (1907-1978) (Scotland, 1971)
For more than fifty years and for millions of readers around the world, the New Daily Study Bible commentaries have been the ideal help for both devotional and serious Bible study. William Barclay's brilliant communication, down-to-earth approach, and sheer enthusiasm have inspired generations of readers. These new editions contain a new foreword from renowned theologian and author Alister McGrath, along with updated language to clarify less familiar illustrations from the originals and the inclusion of more contemporary language.
Keywords: Bible -- Philippians -- Commentaries